First-Principle Insight into the Ru-Doped PtSe(2) Monolayer for Detection of H(2) and C(2)H(2) in Transformer Oil - Li, Dajian (ACS Omega, 2020)
[Image: see text] Using first-principles theory, this paper investigates the sensing behavior of the Ru-doped PtSe(2) (Ru-PtSe(2)) monolayer for two dominant gases, namely, H(2) and C(2)H(2), in the transformer oil to explore its potential as a gas sensor to evaluate the operation status of the electrical transformers. Ru-doping prefers to go through the S(1) site with the largest E(b) of −3.71 eV. Chemisorption is identified in the H(2) and C(2)H(2) systems with E(ad) obtained as −0.83 and – 2.09 eV, respectively, indicating the stronger performance of the Ru-PtSe(2) monolayer upon C(2)H(2) adsorption. Meanwhile, the obvious improvement of bandgap in the C(2)H(2) system suggests the potential of Ru-PtSe(2) monolayer as a resistance-type gas sensor for C(2)H(2) detection. Moreover, the applied biaxial strains ranging at 1–5% give rise to various Q(T) and E(g) in two systems, indicating the tunable sensing response of the Ru-PtSe(2) monolayer for gas detection with modulated strains. Our calculation proposes a novel 2D sensing material for H(2) and C(2)H(2) detection, which would be beneficial to stimulate more edge-cutting research in the gas sensing field as well.